Alih Kode dan Campur Kode dalam Film Budi Pekerti 2023 - Aziza Ula Fallahi (ESTETIK : Jurnal Bahasa Indonesia, 2025)
Language becomes a vital communication tool in social interaction of multilingual society like Indonesia, code switching and code mixing phenomena are common, especially in entertainment, including film. Film as a representation of daily life often contains linguistic practices that reflect the social and cultural dynamics of society. The film "Budi Pekerti" displays the use of language variety in various communication situations. This study aims to analyze the form of code switching and code mixing in dialogue between film characters, and to identify the social and communicative functions of its use. This study uses a qualitative approach with a descriptive method. Using observation data sources on dialogue in the film which is transcribed and analyzed sociolinguistically. The data collection technique uses the listen-read-note technique. This study produced findings, there were 36 data obtained, 7 of which were in the form of code switching and 29 were in the form of code mixing. The data also showed that no external code switching was found. Then, an analysis of the social and communicative function of the use of code switching and code mixing was found. The phenomenon of code switching and code mixing occurs in order to show the speaker's social identity, create intimacy and emotional closeness, emphasize intentions and convey emotions, and finally, it can implicitly improve the language style and aesthetics of the film. These findings reinforce the important role of film as a medium for reflection on linguistic practices in bilingual and multicultural societies.